Incentive-compatible voting rules with positively correlated beliefs : correction - Abhigyan Bose; Souvik Roy (Theoretical Economics, 2022)
Theorem 1 in Bhargava, Mohit et al. (2015) provides a necessary condition for a social choice function to be LOBIC with respect to a belief system satisfying top-set (TS) correlation. In this paper, we provide a counter example to that theorem and consequently provide a new necessary condition for the same in terms of sequential ordinal nondomination.
Keywords: D71; D82; 330; Ordinal Bayesian incentive compatibility; correlated beliefs; sequential ordinal nondomination property